Wakaf Digital Malaysia: Hadis, Rantai Blok dan Visi Ekosistem Filantropi Berterusan: Digital Waqf Malaysia: Hadith, Blockchain and the Vision of a Sustainable Philanthropic Ecosystem - Zaim Sabirin Yusoff; Siti Nurwanis Mohamed; M. Riza Muarrif; Siti Nuroni Mohamed; Khairul Fawwaz Mat Taib; Ahmad Junaidi Che Ariffin (RABBANICA - Journal of Revealed Knowledge, 2025)
This study examines the framework of digital waqf in Malaysia, emphasising the hadith of Umar r.a. as the primary and most authoritative legal source. It aims to analyse the hadith text to extract key waqf principles, particularly the preservation of the principal asset and the ongoing distribution of benefits, and to integrate these principles with modern digital innovations. Using a qualitative methodology through in-depth content analysis, the study relies on primary sources from classical hadith and fiqh literature, with secondary sources providing context for technological applications. The findings are organised into three main dimensions: firstly, it discusses the fundamental hadith principles of waqf; secondly, it explores the integration of hadith-based fiqh with digital waqf; and thirdly, it presents a vision for developing a comprehensive ecosystem to realise the concept of ṣadaqah jāriyah. The research concludes that the success and validity of any digital waqf initiative in Malaysia depend entirely on adherence to the principles derived from the hadith of Umar r.a. The analysis indicates that blockchain technology has the potential to serve as a Shariah-compliant tool for safeguarding the perpetuity of waqf assets, while enhancing efficiency, transparency, and integrity in management. However, further empirical evidence is needed to validate its practical effectiveness. Additionally, structural and systemic challenges, such as inconsistencies in legal frameworks and the necessity for robust Shariah governance, must be addressed. This study contributes to the literature by providing fiqh-based and conceptual references for the development of digital waqf, without claiming the creation of new theories. The findings suggest that successful transformation requires a holistic approach, including standardised governance frameworks and technological integration supported by rigorous Shariah oversight. This research is particularly relevant for policymakers, waqf institutions, and Shariah authorities. Kajian ini meneliti kerangka wakaf digital di Malaysia dengan tumpuan utama kepada Hadis Umar r.a. sebagai sumber perundangan tunggal dan terpenting. Kajian ini bertujuan menganalisis teks Hadis Umar r.a. bagi mengekstrak prinsip-prinsip wakaf yang relevan, terutamanya ḥabsu al-aṣl dan tasbīl al-thamar, seterusnya mengintegrasikannya dengan inovasi digital. Menggunakan pendekatan kualitatif dengan reka bentuk analisis kandungan yang mendalam, data primer dikumpul daripada kitab hadis dan fiqh, manakala data sekunder digunakan untuk konteks aplikasi teknologi. Dapatan kajian ini dibahagikan kepada tiga aspek utama iaitu: [Pertama]: Asas dan prinsip hadis wakaf; [Kedua]: Fiqh hadis dan waqaf digital; dan [Ketiga]: Visi ekosistem dalam merealisasikan ṣadaqah jāriyah. Hasil kajian menunjukkan bahawa kejayaan dan kesahihan mana-mana platform wakaf digital di Malaysia bergantung sepenuhnya pada pemeliharaan prinsip asas Hadis Umar r.a.. Analisis mendapati teknologi blok rantai mempunyai potensi untuk berfungsi sebagai instrumen yang selari dengan syariah dalam menjamin keutuhan harta wakaf serta meningkatkan aspek kecekapan, ketelusan dan integriti pengurusan, walaupun bukti empirikal lanjut masih diperlukan untuk mengesahkan keberkesanan praktikalnya. selain itu, cabaran struktur dan sistemik seperti ketidakseragaman undang-undang serta keperluan tadbir urus syariah yang kukuh perlu ditangani. Kajian ini menyumbang kepada literatur dengan menyediakan asas rujukan fiqh dan konseptual bagi pembangunan wakaf digital, tanpa mendakwa pembinaan teori baharu. Dapatan mencadangkan bahawa transformasi yang berjaya memerlukan pendekatan holistik, termasuk rangka kerja tadbir urus yang seragam dan integrasi teknologi yang disokong oleh pengawasan syariah yang ketat. Kajian ini relevan untuk pembuat dasar, institusi wakaf dan pakar syariah dalam usaha memajukan ekosistem wakaf digital yang patuh syariah di Malaysia.